A comunicação no contexto da mudança cultural: um estudo de caso do Instituto Federal de Educação, Ciência e Tecnologia Goiano - Faria, Cláudia Sousa Oriente de (2015)
Purposed of this research was to analyze and understand communication, specifically internal communication in force at the Federal Institute of Education, Science and Technology Goiano (Goiano IF) in the context of change in their culture, which occurred after the implementation of Law No. 11,892, of 29 December 2008. In addition to the analysis itself communication, we sought to further identify, through the established communication, the present culture in IF Goiano to collaborate so that the IF has Goiano subsidies to better understand their communication . We chose this theme to realize that the changes that happen in organizations have a strong influence on culture and internal communication of the place. In this investigation the IF Goiás and the communication issued by him were viewed and analyzed in a multidimensional way, and the IF Goiano empirical object and the communication theoretical object. Was elected case study as the work methodology more appropriate to understand the communication IF Goiano. The choice of this approach has involved the use of instruments of a qualitative nature, which did not prevent the use of quantitative tools. To this end the following techniques were adopted: bibliographic research, documentary and institutional or administrative; diary; and field research, using interviews and sending online questionnaires. It is said that IF Goiano was analyzed as a communication transmitter from formal aspects, taking advantage of the institutional and administrative dimension, communing of thought about the complexity of Edgar Morin, one of the authors that underpin this study. It is emphasized that the communication in this research, was seen as an opportunity to (re) construction of the scenario, as well as the Goiano IF culture that is constantly building process through communication, considering that communication and its culture are mutually influencing the other.